Comparative analysis of the political activity of the Polish minority in Ukraine and the Ukrainian minority in Poland in 1990-2015 (based on pilot studies from 2014-2015) = Analiza porównawcza aktywności politycznej mniejszości polskiej na Ukrainie oraz mniejszości ukraińskiej w Polsce w latach 1990-2015 (na podstawie badań pilotażowych z lat 2014-2015) - Łodziński, Sławomir; Rudnicki, Sergiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article tries to analyze the participation and political representation of the Polish minority in Ukraine and the Ukrainian minority in Poland in the period 1990-2015. Its meaning stems from at least several reasons. Firstly, because the both states officially accepted national minorities after 1990, they have introduced institutional arrangements of protection of their rights and have signed the major international documents in this area. Secondly, because the process of adaptation of European standards of minority protection took place in both countries in the situation of deep democratic changes and market reforms.
Keywords: political activity; political representation; protection of national minorities; Ukrainian minority in Poland; Polish minority in Ukraine; aktywność polityczna; reprezentacja polityczna; ochrona mniejszości narodowych; mniejszość ukraińska w Polsce; mniejszość polska na Ukrainie